2012
DOI: 10.1021/ct200880m
|View full text |Cite
|
Sign up to set email alerts
|

Graphite and Hexagonal Boron-Nitride have the Same Interlayer Distance. Why?

Abstract: Graphite and hexagonal boron nitride (h-BN) are two prominent members of the family of layered materials possessing a hexagonal lattice structure. While graphite has nonpolar homonuclear C−C intralayer bonds, h-BN presents highly polar B−N bonds resulting in different optimal stacking modes of the two materials in the bulk form. Furthermore, the static polarizabilities of the constituent atoms considerably differ from each other, suggesting large differences in the dispersive component of the interlayer bondin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
196
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(211 citation statements)
references
References 106 publications
14
196
0
1
Order By: Relevance
“…Many efforts have been dedicated towards the understanding of the interlayer binding in graphite [13][14][15][16][17][18][19][20][21][22][23] and its dependence on the layer stacking. [24][25][26][27] Here we consider some of the most widely used numerical methods to describe graphite/FLG and compare their description of the potential corrugation.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been dedicated towards the understanding of the interlayer binding in graphite [13][14][15][16][17][18][19][20][21][22][23] and its dependence on the layer stacking. [24][25][26][27] Here we consider some of the most widely used numerical methods to describe graphite/FLG and compare their description of the potential corrugation.…”
Section: Introductionmentioning
confidence: 99%
“…We further extract the distance below graphene, ∼2.0 Å, at which the electric field is essentially unscreened. This distance is relevant for other layered materials with similar interlayer distances [39].…”
mentioning
confidence: 96%
“…As a result, it often fails to describe the intermolecular interaction and phenomena arising from it (e.g., sublimation and physisorption). It has been shown that a proper vdW correction can significantly improve the performance of conventional DFT, greatly extending its applicability to a broader class of problems such as molecular complexes and solids [2][3][4][5][6][7][8][9] and layered materials. 10,11 The vdW interaction is an important long-range nonlocal correlation arising from instantaneous charge fluctuations on each density fragment.…”
mentioning
confidence: 99%